From big data to econophysics and its use to explain complex phenomena - Paulo Ferreira; Éder J. A. L. Pereira; Hernane B. B. Pereira (Journal of Risk and Financial Management, 2020)
Big data has become a very frequent research topic, due to the increase in data availability. In this introductory paper, we make the linkage between the use of big data and Econophysics, a research field which uses a large amount of data and deals with complex systems. Different approaches such as power laws and complex networks are discussed, as possible frameworks to analyze complex phenomena that could be studied using Econophysics and resorting to big data.
Keywords: 330; big data; complexity; networks; power laws; stock markets